Crime and normlessness : an attempt to isolate conditions of anomie - Midgley, James (Department of Sociology, 2024)
The work presented here is an original contll"ibution to an established theoll"y of crime and deviant behaviour - the theory of anomie. It begins by discussing some fundamental problems in the study of crime and pmceeds to argue that the sociological interpretation is one of the most comprehensive and useflll approaches in modem criminology. · While the theory of anomie has considerable status among sociological theories of crime, it is suggested that one of its most serious drawbacks is the way in which terms and meaning have been confused and inadequately operationalized for· the pull'poses of researdi • . The work presented here makes a contribution to the theory of anomie and research into it, by attempting to analyse and clarify theoretical meanings and operational definitions; by· formulating a theoretical conception and suitable operational measure of anomie; by applying this measure in an empirical setting and demonstrating that conditions of anomie may be isolated; by subiecting the main propositions of Robert Merton1 s_theory to empirical test. It is, therefore, a contribution to both the9ry and reseorch into anomie. / It is possible that the use of the Coloured population of Cape Town as research subjects may mislead the reader. The research reported here is not an attempt to explain high rates of crime and deviance in the Coloured population. It is not even attempting to suggest that the theory of anomie is a suitable model for explaining crime and deviance in '.South African society. From another perspective the research attempted todemonstratedthat the concept of anomie might be empirically operationalized, that conditions of anomie might be isolated in the real world and that the theory of anomie might be subiected to empirical test. In this way it constituted an original contribution to knowledge.